Observation to Openness: Governing Hydrological Data in a Non-Stationary World - R. Neupane, Bhanu; Pradhananga, Dhiraj (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
The movement from observation to openness has become a defining challenge in environmental sciences. This challenge is particularly acute for hydrological governance in a non-stationary world. The assumptions underpinning water management, planning, and infrastructure design have been increasingly challenged by climatic variability, land-use change, and urbanization. These pressures have increased both the volume of environmental data produced and the strategic importance of governing that data effectively. However, hydrological data systems remain dispersed across institutions, scales, and jurisdictions. This paper argues that the transition from observation to openness is no longer a secondary technical reform but a core condition for water security, scientific reproducibility, risk governance, and equitable adaptation. Using a systems lens, it examines the full hydrological observation and data lifecycle and shows how bottlenecks at any stage can undermine decision-making. The paper then interrogates the quality-versus-quantity debate under conditions of non-stationarity, uncertainty, and the abundance of multi-source data, emphasizing that openness without metadata, standards, and accountability can reproduce rather than address epistemic weaknesses. A new governance paradigm is proposed, anchored in FAIR data principles, interoperability, public-value logic, and the doctrine of openness, as open as possible, and as closed as necessary. Particular attention is given to transboundary hydrology, data sovereignty, institutional asymmetries, and the growing need for trusted cross-border data flows. The paper concludes with a layered policy agenda for Member States, distinguishing what should, might, or can be done. Its central claim is that, in a non-stationary world, hydrological observation achieves full public value only when it is embedded in a culture of governed openness.
Keywords: Anthropocene; Environmental Data; Open Data; Hydrological Data Governance; FAIR; Interoperability; Non-stationarity; Water Security; Metadata; Digital Public Infrastructure